Doktrin Single Economic Entity dalam Perluasan Pengawasan Persaingan Usaha secara Ekstrateritorial di Indonesia - Dirwansyah Dirwansyah (Fakultas Hukum, Universitas Warmadewa, 2024)
The ambiguity of the single economic entity doctrine in Indonesian competition law leads to the perception that it is neither recognized nor applied, hindering enforcement. To avoid formal debates on absolute competence and reduce legal voids causing uncertainty, explicit and written regulation of this doctrine is necessary. As a civil law country, the inability of foreign holding companies to be accountable for anti-competitive control over subsidiaries creates legal uncertainty. Ideal parameters for assessing a single economic entity include economic interest relationships through share ownership and joint ventures, and business decision independence. Controlled entities are viewed as representatives of controlling entities. The doctrine aims to identify primary anti-competitive actors. If controllers prove the absence of anti-competitive instructions, they may be exempt from accusations. Penalties for controlling entities should not exceed those for controlled entities.